The Effect of Clomid (Ciomiphene Citrate) on Chickens: III. Sexual Characteristics in the Male - SHANAWANY, M. M.; AL-KHAZRAJI, A. K.; HAMED, O. (The Libyan Journal of Agriculture, 2023)
The effects of daily force-feeding 2 mg/bird of clomid (ciomiphene citrate)2 were investigated using sixty, 12-week old. Single Comb White Leghorn-type cockerels. Force-feeding of clomid significantly improved body weight gain and feed efficiency of the cockerels. Between the treatment means no significant differences were found in respect to feed consumption. Clomid severly decreased comb and testis weights. Also daily injection of 20 ug dehydro-epi-androsterone to cockerels fed clomid reduced comb and testicular weight significantly but to a lesser degree than clomid alone. On the other hand, adrenals and thyroids weights were significantly increased. Though liver weight was not significantly affected in treated cockerels, the cytological studies using PAS and osmic acid indicated a reduction in liver glycogen accompanied by an increase in fat deposition. Additionally, the spectrophotometric determination of plasma glucose showed that clomid treated cockerels had significant lower glucose levels.